NARASI SUSI PUDJIASTUTI DI MEDIA: SEBUAH PERJUMPAAN DIALEKTIS (Susi Pudjiastuti's Narrative in Media: A Dialectical Encounter) - Kholila, Ainun; Hafidzulloh, M (Kandai, 2023)
The coverage of Susi Pudiastuti in various online media regarding her ability to become the ministry of marine affairs and fisheries  in the second period has generated various polemics. These problems arise because the narratives built from various media are often different from one another. This distinction has resulted in various perspectives materializing to translate how the discourse construction is behind the statement text. This study will analyze how the discourse form of media content narrates Susi Pudjiastuti as a minister in the second period. The data explored are the media narratives of Kumparan.com, Wartaekonomi.com, Tribunnews, Liputan6.com, Theconversation.com, Kompas.com. Textual data from some of these media will be analyzed using Norman Fairclough's critical discourse analysis approach. Media text narratives that are the research object will be positioned as constructing public discourse by examining and describing discourse practices from online media narratives. This study found that the online media that reported Susi Pudjiastuti's willingness contained discourse production, directing to justification and public opinion formation. The discourse present in the text provides an argumentative basis that always presupposes a social change regarding the perspective produced to find the dialectic of discourse and transformation in the form of discursive practice. Pemberitaan Susi Pudiastuti di berbagai media online terkait kesanggupan menjadi menteri perikanan dan kelautan pada periode kedua menuai beragam polemik. Problematika tersebut hadir karena narasi yang dibangun dari berbagai media seringkali berbeda antar satu dan lainnya. Perbedaan itu menuai beragam perspektif bermunculan untuk menerjemahkan bagaimana konstruksi wacana yang hadir di balik teks berita. Penelitian ini mengupas bagaimana bentuk wacana dari konten media yang menarasikan Susi Pudjiastuti sebagai menteri pada periode kedua. Data yang dianalisis adalah narasi media Kumparan.com, Wartaekonomi.com, Tribunnews.com, Liputan6.com, Theconversation.com, dan Kompas.com. Data tekstual dari beberapa media tersebut dianalisis dengan pendekatan analisa wacana kritis Norman Fairclough. Narasi teks media yang menjadi objek penelitian diposisikan sebagai pembentuk wacana publik dengan menelaah dan mendeskripsikan praktik wacana dari narasi media online. Penelitian ini menemukan bahwa media online yang memberitakan kesediaan Susi Pudjiastuti ini memuat produksi wacana yang mengarah kepada pemberian justifikasi dan membangun opini publik. Ikhwal wacana yang hadir dalam teks memberikan dasar argumentatif yang senantiasa mengandaikan adanya perubahan sosial mengenai perspektif yang dibangun untuk menemukan dialektika wacana dan transformasi dalam bentuk praktik diskursif.